Reflections on teaching Urdu in Germany - Oesterheld, Christina (Economic & political weekly, 2002)
Although Urdu is taught in German universities, students who opt for it are only those who want to embark on historical studies. To a scholar wanting to study India a knowledge of Urdu is of practically no importance. The concept of Urdu as primarily or even exclusively a literary language, a language of love poetry, of refinement and elegance causes much damage to the way Urdu instruction is designed. It also helps in trivialising Urdu literature, particularly ghazal and qawwali. Urdu needs to be projected as a modern language.
Gesehen am 25.06.2021